2018
DOI: 10.3390/molecules23051118
|View full text |Cite
|
Sign up to set email alerts
|

Lipase-Catalyzed Synthesis of Sucrose Monolaurate and Its Antibacterial Property and Mode of Action against Four Pathogenic Bacteria

Abstract: The aim of this work was to evaluate the antibacterial activities and mode of action of sucrose monolaurate (SML) with a desirable purity, synthesized by Lipozyme TL IM-mediated transesterification in the novel ionic liquid, against four pathogenic bacteria including L. monocytogenes, B. subtilis, S. aureus, and E. coli. The antibacterial activity was determined by minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), and the time–kill assay. SML showed varying antibacterial activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Moreover, physical changes occur at reduced temperatures; it is possible that the listerial cell wall and membranes become less malleable or interactive at lower temperatures thus less permeable to a carbohydrate ester. Recently Shao [11] investigated the antimicrobial activity of sucrose monolaurate against L. monocytogenes. They showed that the sucrose ester caused pronounced damage to the cell membrane integrity and may form a hole in the peptidoglycan layer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, physical changes occur at reduced temperatures; it is possible that the listerial cell wall and membranes become less malleable or interactive at lower temperatures thus less permeable to a carbohydrate ester. Recently Shao [11] investigated the antimicrobial activity of sucrose monolaurate against L. monocytogenes. They showed that the sucrose ester caused pronounced damage to the cell membrane integrity and may form a hole in the peptidoglycan layer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research [4] [8] [9] [10] [11] has documented the bactericidal/inhibitory activity of carbohydrate esters in growth media. Our lab was the first to enzymatically synthesize lactose esters [12] and shows the microbial inhibitory properties of lactose monolaurate (LML) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Efforts are continuing to make and establish them as safe therapeutic drugs [3][4][5]. Many esters, known as sugar esters (SEs), are known for their multiple surfactants [6,7], and biological properties [8][9][10][11]. These are mainly used as nonionic type surfactants [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…These are mainly used as nonionic type surfactants [6,7]. Different biological properties and applications are reported by many researchers [10,11]. The most common structural features of SEs are the combination of hydrophilic and hydrophobic parts [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation